Evolution of a large, conserved, and syntenic gene family in insects. - Shah, N.; Dorer, D.R.; Moriyama, E.N.; Christensen, A.C. (G3 : genes - genomes - genetics, 2012)
The Osiris gene family, first described in Drosophila melanogaster, is clustered in the genomes of all Drosophila species sequenced to date. In D. melanogaster, it explains the enigmatic phenomenon of the triplo-lethal and haploinsufficient locus Tpl. The synteny of Osiris genes in flies is well conserved, and it is one of the largest syntenic blocks in the Drosophila group. By examining the genome sequences of other insects in a wide range of taxonomic orders, we show here that the gene family is well-conserved and syntenic not only in the diptera but across the holometabolous and hemimetabolous insects. Osiris gene homologs have also been found in the expressed sequence tag sequences of various other insects but are absent from all groups that are not insects, including crustacea and arachnids. It is clear that the gene family evolved by gene duplication and neofunctionalization very soon after the divergence of the insects from other arthropods but before the divergence of the insects from one another and that the sequences and synteny have been maintained by selection ever since.